Effect of ethanolic extract of Andrographis paniculata (Burm.F.) nees on a combination of fat-fed diet and low dose streptozotocin induced chronic insulin resistance in rats - Subramanian, Rammohan (Array, 2008)
Summary: Andrographis paniculata ethanolic extract was evaluated to screen the effect on insulin resistance using a combination of fat-fed diet and low dose streptozotocin. The glucose-insulin index as a measure of insulin action on glucose disposal rate was calculated during the intraperitoneal glucose tolerance test. Oral administration of 1000 mg/kg extract to rats was able to cause a significant (p<0.05) reduction of elevated glucose-insulin index, signifying a potential insulin sensitizing effect. Oral administration of the extract at a dose of 1000 mg/kg once daily for 30 days to streptozotocin-diabetic rats increased the hypoglycemic responses to incremental dosing of exogenous insulin, thus causing an increase in insulin sensitivity. The results seem to suggest that oral administration of Andrographis paniculata ethanolic extract may have the ability to improve insulin sensitivity and delay the development of insulin resistance, and may thus have a role in amelioration of insulin resistance in patients. However, its potential use in humans can only be validated by thorough investigation